(untitled) (Law and world, 2015)
After discussing to practice legislative charges of Labour Code Of Georgia judicial problems have caused.There are reviewed the ways of solution which are relevant to society and it will promote common judicial practice. Social dialogue is one of the major indicators for determining of democracy, the significant part of society represent the working people-employees, who create wealth and contribute to the preservation of the country’s stable economic sustainability.